Analyzing the Influence of Critical Thinking Skills, Self-Efficacy, Digital Literacy, and Industrial Internship on Students' Work Readiness: SEM-PLS Approach - Aryasandy, Nensy; Arwizet, Arwizet; Ambiyar, Ambiyar; Sukardi, Sukardi; Rozi, Fakhrur (Jurnal Pendidikan MIPA, 2025)
This quantitative study investigates the influence of critical thinking skills, self-efficacy, digital literacy, and internship experience on work readiness among vocational high school students. This research is motivated by the persistently high unemployment rates among vocational graduates in Indonesia, which reflect a gap between the skills acquired in school and those demanded by the job market. of the study involved 143 twelfth-grade students from SMK Negeri 2 Sungai Penuh and employed an explanatory quantitative approach. Data were collected using a structured questionnaire and analyzed through Structural Equation Modeling (SEM) using SmartPLS 3.0. The findings confirmed that the measurement model satisfied the required criteria for reliability, convergent validity, and discriminant validity. The structural model testing indicated that critical thinking skills, self-efficacy, and internship experience significantly and positively influenced work readiness, while digital literacy did not demonstrate significant effect. Furthermore, self-efficacy was found to partially mediate the correlation between critical thinking and internship experience with work readiness, although the effect sizes of these mediations were relatively small. These results emphasize the importance of enhancing critical thinking, building self-efficacy, and improving the quality of internship programs in the industry to increase vocational graduates' employability. The study highlights that fostering these factors in vocational education can better prepare students for the workforce. Future research is recommended to explore additional external factors that may influence work readiness, such as socio-economic status, personal motivation, or family background, and to broaden the sample size to improve the generalizability of the findings to a larger population.    Keywords: critical thinking skills, self-efficacy, digital literacy, industrial internship, students' work readiness.